At-home bleaching versus whitening toothpastes for treatment of tooth discoloration: a cost-effectiveness analysis - Mariana Evangelista SANTOS; Rênnis Oliveira da SILVA; Yuri Wanderley CAVALCANTI; Sônia Saeger MEIRELES (University of São Paulo, 2024)
Abstract Objectives This study aimed to analyze the cost-effectiveness of whitening toothpastes and at-home bleaching for the treatment of tooth discoloration. Methodology A cost-effectiveness economic analysis was conducted, and eight randomized clinical trials were selected based on the whitening agent product used: blue covarine dentifrices (BCD), hydrogen peroxide dentifrices (HPD), dentifrices without bleaching agents (CD, negative control), and 10% carbamide peroxide (CP10, positive control) for at-home bleaching. The consumer/patient perspective was adopted, macro-costing techniques were used and a decision tree model was performed considering the costs in the American and Brazilian markets. The color change evaluation (ΔE*ab) was used to calculate the effectiveness of tooth bleaching. A probabilistic analysis was performed using a Monte Carlo simulation and incremental cost-effectiveness ratios were obtained. Results CP10 resulted in the highest cost-effectiveness compared to the use of dentifrices in both markets. In Brazil, HPD was more cost-effective than BCD and CD. In the US, the increased costs of HPD and BCD did not generate any whitening benefit compared to CD. Conclusions CP10 was more cost-effective than BCD and HPD for tooth bleaching from the perspectives of the Brazilian and American markets. Decision-making should consider the use of CP10 for treating tooth discoloration.